Integrated NDI-based Controller and Incremental Control Allocation for an eVTOL - Enenakpogbe, Emmanuel (Cranfield University, 2024)
The concept of urban air mobility (UAM) has been proposed to address the transport problems of congestion and pollution in ever-growing urban conurbations. Mature fixed wing aircraft technologies have many constraints that limit their applicability for UAM hence piloted all electric vertical take-off and landing (eVTOL) vehicles known as eVTOL ‘air-taxis’ provide a promising option being lighter, quieter, potentially having net zero emissions and with lower operating costs. Furthermore, their higher bandwidth thrust actuation allows for novel config urations. However, one challenge of eVTOL aircraft operation is their strong nonlinear flight dynamics since they operate over a wide range of operating envelope. One particularly chal lenging eVTOL configuration is the Lilium jet, a fixed-wing, over-actuated vectored thrust, canard light sports aircraft. However, its canard configuration can destabilize the short-period mode requiring fly-by-wire stability augmented flight control systems. A second challenge of this configuration is the coupling between the aerodynamic surface control and the vectored thrust makes control allocation (CA) during transition very difficult. A third challenge of this configuration is its high degree of over-actuation presents a challenging CA. Finally, a fourth challenge of the eVTOL configuration is that the vectored thrust results in nonlinear effector mapping preventing the direct use of classical CA approaches. In order to address the control challenges of the Lilium-style eVTOL, a novel full-envelope controller is presented which em ploys a generic control architecture applicable to piloted, semi-automatic and fully automated flight. The full-envelope controller consist of an aircraft-level controller which produces an overall control demand and a CA scheme which allocates the overall control demand to indi vidual redundant effectors. The CA scheme also performs control error minimisation, control channel prioritization and control effort minimization. The aircraft-level controller adopts a modular approach, consisting of a main inner-loop nonlinear dynamic inversion (NDI) con troller which cancels the bare airframe dynamics and an outer-loop proportional-integral (PI) linear controller which together addresses several of the eVTOL operation challenges. The inner-loop NDI controller is a velocity controller while the outer-loop PI controller is an at titude and navigation position controller which together are used for hover/low speed control and forward flight. This thesis proposes and initially conceptually tests three real-time CA ap proaches for transforming a nonlinear CA problem to a linear problem and then applies active set linear CA technique to address all the remaining challenges of the eVTOL configuration. This thesis fully verifies one of the CA approaches on a full six-degrees-of-freedom model version of the eVTOL aircraft. Simulation results clearly demonstrates that the controller has reasonable disturbance rejection, can guarantee stable flight in case of severe actuator satura tion and has satisfactory compliance to typical mission tasks for this class of vehicle
Lu, Linghai - Associate supervisor
Keywords: active set; actuator saturation; nonlinear effector mapping; vertical takeoff and landing (VTOL); air-taxi; urban air mobility (UAM); transition; over-actuated; virtual controls; full envelope; effector model; weighted least squares (WLS); optimal; high level controller; unified con trol framework; real-time; online; linear time varying (LTI) constrained optimisation; linear quadratic programming